INFECTIOUS BURSAL DISEASE AND NEWCASTLE DISEASE CO-INFECTION WITH COLISEPTICEMIA IN A 15-WEEK-OLD COMMERCIAL LAYER CHICKEN - Dimas Kholis Prasetiyo; I Made Kardena; Ida Bagus Kade Suardana; I Nengah Kerta Besung; Ni Luh Putu Diah Septianingsih (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Infectious Bursal Disease (IBD) and Newcastle Disease (ND) are major threats to the poultry industry due to their high mortality rates. These diseases often become more complex when accompanied by bacterial coinfections that further compromise the health status of affected birds. A 15-week-old laying hen exhibited clinical signs including anorexia, decreased egg production, lethargy, diarrhea characterized by watery greenish-white feces, nasal exudate, incoordination, swelling of the frontal and orbital sinuses, and torticollis. Epidemiological analysis revealed a morbidity rate of 5.7%, a mortality rate of 5.1%, and a case fatality rate of 88%. Gross pathological examination demonstrated multiorgan hemorrhage, congestion, hyperemia, petechial hemorrhages in the proventriculus, and enlargement of the bursa of Fabricius accompanied by black discoloration. Histopathological examination revealed inflammatory cell infiltration dominated by lymphocytes in nearly all organs and by heterophils in several tissues. Laboratory testing of bursal tissue using chicken embryo fibroblast cell cultures showed cytopathic effects, indicating IBD virus replication. The hemagglutination (HA) test yielded a titer of 2⁵, and the hemagglutination inhibition (HI) test confirmed the presence of ND virus. Bacterial cultures from the intestine, liver, and lungs identified Escherichia coli, indicating the occurrence of colisepticemia. It can be concluded that the hen was affected by concurrent IBD and ND virus infections, which were further exacerbated by colisepticemia.